Electrospinning‐Based Strategies for Battery Materials. Issue 2 (24th June 2020) - Li, Xiaoyan; Chen, Weichen; Qian, Qingrong; Huang, Haitao; Chen, Yuming; Wang, Ziqiang; Chen, Qinghua; Yang, Jing; Li, Ju; Mai, Yiu‐Wing
Abstract: Electrospinning is a popular technique to prepare 1D tubular/fibrous nanomaterials that assemble into 2D/3D architectures. When combined with other material processing techniques such as chemical vapor deposition and hydrothermal treatment, electrospinning enables powerful synthesis strategies that can tailor structural and compositional features of energy storage materials. Herein, a simple description is given of the basic electrospinning technique and its combination with other synthetic approaches. Then its employment in the preparation of frameworks and scaffolds with various functions is introduced, e.g., a graphitic tubular network to enhance the electronic conductivity and structural integrity of the electrodes. Current developments in 3D scaffold structures as a host for Li metal anodes, sulfur cathodes, membrane separators, or as a 3D matrix for polymeric solid‐state electrolytes for rechargeable batteries are presented. The use of 1D electrospun nanomaterials as a nanoreactor for in situ transmission electron microscopy (TEM) observations of the mechanisms of materials synthesis and electrochemical reactions is summarized, which has gained popularity due to easy mechanical manipulation, electron transparency, electronic conductivity, and the easy prepositioning of complex chemical ingredients by liquid‐solution processing. Finally, an outlook on industrial production and future challenges for energy storage materials is given. Abstract : Recent advances in electrospinning combined with other materials processing techniques toward a powerful synthesis strategy that can tailor structural and compositional features are summarized for their energy storage applications. The synthesized nanomaterials can also work as nanoreactors for in situ transmission electron microscopy characterization, that enables an understanding of the mechanisms of the materials synthesis process and electrochemical reaction behaviors related to energy storage applications.